(untitled) (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2025)
Welding is the process of joining 2 metals using a heat process. Ship repair is a ship care and maintenance activity that is planned periodically in accordance with the requirements of the classification body. It is not uncommon for a shipbuilding industry to carry out replating procedures that do not comply with the regulations of the classification body. It is often found in the replating process that plate joints have angles of less than 90°. This research explores the effect of the cutting angle of ship hull plates on the stress distribution in welded joints of ship hull plates using the finite element method with Solidworks simulation software using ASTM A36 material, taking angles of 30°, 40°, 50°, 60°, 70°, 90°. Based on the test results using Solidworks, we can see that the minimum stress results are at a 30o angle variation with a value of 92.6 N/mm2, and the maximum value is at a 90o angle with a value of 281 N/mm2. With several variations of these angles, those that meet BKI standards are the 80o angle and the 90o angle, each of which has a yield strength value that meets the standards set by the classification. To ensure the safety and durability of the ship’s plate, it is recommended that the plate be cut at an 80° or 90° angle. These corners not only meet BKI standards but also demonstrate a more stable and even stress distribution, reducing the risk of material failure.